Institutional Reconstruction of the House of Representatives: A Constitutional Critique and the Crisis of Popular Representation - Mustawan, Fauziana; Kamal, Muhammad; Mustamin, Mustamin (CV. Social Politic Genius (SIGn), 2025)
The DPR, as the manifestation of popular sovereignty, is currently facing intense scrutiny due to structural dysfunction in the execution of its three functions. This study aims to analyze the constitutional critique of legislative dysfunction, oversight paralysis, and the crisis of representation under political party hegemony, and to formulate a concept for institutional reconstruction through an amendment to the relevant Law. Employing doctrinal legal research with statutory, conceptual, and comparative approaches, this research dissects the disparity between the constitutional design of the 1945 Constitution and the implementation reality of Law Number 17 of 2014. The results indicate that the DPR for the 2019-2024 period experienced legislative hegemony characterized by hyperregulation and absolute dominance over the DPD within a soft bicameral system. Furthermore, the oversight function was paralyzed by procedural hurdles regarding the Right of Inquiry quorum and by political subordination to the executive. The fundamental root of the problem lies in the crisis of representation, where the constitutional mandate of people’s representatives has been degenerated by party sovereignty through a unilateral recall mechanism. This study concludes that institutional reconstruction cannot be pursued through institutional dissolution, but must proceed through regulatory reform encompassing the application of a regulatory guillotine, reformulation of Right of Inquiry requirements, abolition of member impunity, and tightening of recall conditions. The main recommendation is to amend Law Number 17 of 2014 to restore the checks-and-balances mechanism and restore the dignity of the DPR as the mouthpiece of the people.